Lexical Characteristics of the Belarusian Translation of Chapters 6–9 of the Gospel of Matthew (Orthodox and Catholic Editions) - Eugeniusz Pankow (Zeszyty Cyrylo-Metodiańskie)
The article provides a comparative analysis of lexical and certain grammatical peculiarities in the Catholic and Orthodox editions of the Belarusian translation of chapters 6–9 of the Gospel of Matthew. The study is based on biblical textual sources in Belarusian, Polish, Russian, Greek, and Hebrew, including explanatory and other dictionaries, as well as works on modern Belarusian literary lexicology. The study reveals that while adapting the Gospel of Matthew into Belarusian, translators exhibit a certain dependence on foreign languages’ influence and confessional writing traditions, thus sometimes disregarding encyclopedic variants, or ignoring lexical, semantic, and grammatical processes characteristic for the modern Belarusian standard language. Original title in Belarusian: Лексічныя асаблівасці перакладу глаў 6–9 Евангелля паводле Мацвея на беларускую мову (праваслаўная і каталіцкая рэдакцыі).